On Parallelism of Half-Lightlike Submanifolds of Indefinite Kenmotsu Manifolds. (5th June 2013) - Wang, Wenjie; Liu, Ximin
Abstract : We mainly investigate the parallelism of half-lightlike submanifolds of indefinite Kenmotsu manifolds. It is proved that a tangential half-lightlike submanifold M of an indefinite Kenmotsu space form M - c, g - with semiparallel second fundamental form h either satisfies c = - 1 or is J - R a d T M, T M -mixed geodesic.